The faces of God in America: Revealing religious diversity across people and politics. - Joshua Conrad Jackson; Neil Hester; Kurt Gray (PLoS ONE)
Literature and art have long depicted God as a stern and elderly white man, but do people actually see Him this way? We use reverse correlation to understand how a representative sample of American Christians visualize the face of God, which we argue is indicative of how believers think about God's mind. In contrast to historical depictions, Americans generally see God as young, Caucasian, and loving, but perceptions vary by believers' political ideology and physical appearance. Liberals see God as relatively more feminine, more African American, and more loving than conservatives, who see God as older, more intelligent, and more powerful. All participants see God as similar to themselves on attractiveness, age, and, to a lesser extent, race. These differences are consistent with past research showing that people's views of God are shaped by their group-based motivations and cognitive biases. Our results also speak to the broad scope of religious differences: even people of the same nationality and the same faith appear to think differently about God's appearance.